The relationships of olive oil, price of soybean oil, interest rate, price of crude oil, exchange rate, towards the price of crude palm oil in Malaysia (2010-2012) / Mohamad Akib Kasim - Kasim, Mohamad Akib (2013)
Crude palm oil is one of the major commodities that are trade in Malaysia. The fluctuation of its price will affect the overall economic performance and it will cause a trouble to many parties. Instability of CPO prices will cause a big problem in Malaysian economy development and give a significant risk to producers, traders, consumers and others that involve in the production and marketing of CPO. Therefore, in this study, the researcher tries to examine the factors that influence the price of CPO in Malaysia. From this study, there are five determinant factors that could influence the price, which are soybean oil price (SOB), crude oil price (CO), olive oil price (OLO), interest rate (IR) and exchange rate (EX). The study employs Multiple Linear Regression Method to analyze the relationship between all the five independent variables and the dependent, CPO price by using time series data from 2010-2012. All data are collected by monthly basis. The scope of study for the research is based on the agriculture business area, which concentrated on the price of CPO and the factors affecting its price in Malaysia. In this research, the researcher expects that the soybean oil, crude oil, olive oil, interest rate and exchange rate will have strongly significant relationship between the prices of CPO in Malaysia.